Efficacy and safety of anakinra in radiation-induced acute pericarditis: a case report - Sicignano, Ludovico Luca; Murace, Celeste Ambra; Palazzo, Antonella; Verrecchia, Elena; Massaro, Maria Grazia; Manna, Raffaele; Gerardino, Laura (Frontiers in Cardiovascular Medicine, 2024)
Background Acute pericarditis represents an inflammatory disease affecting the pericardial layers. In developed countries more than 80% of pericarditis are defined as idiopathic, less frequently they are secondary to other conditions such as infections, rheumatic or systemic inflammatory diseases, cancer, post–cardiac injury syndromes and radiation therapy (RT). Case presentation We reported a case of a patient with acute pericarditis that occurred a few hours after chest radiation therapy, performed for breast cancer. After the failure of first-line therapy, we introduced anakinra, an anti- interleukin-1 (IL-1) agent, observing an immediate clinical and instrumental response. Conclusions Our experience highlights the efficacy and safety profile of anakinra in early stages of acute pericarditis with an inflammatory phenotype. To the best of our knowledge, there is no data supporting the use of anakinra in the treatment of RT induced acute pericarditis.